Gender differences in the effect of urge‐to‐cough and dyspnea on perception of pain in healthy adults. Issue 8 (August 2014) - Gui, Peijun; Ebihara, Takae; Sato, Ryuhei; Ito, Kumiko; Kohzuki, Masahiro; Ebihara, Satoru
Abstract Previous studies have reported that respiratory sensations, such as urge‐to‐cough and dyspnea, have an inhibitory effect on pain. Considering the existence of gender differences in both urge‐to‐cough and pain, it is conceivable that a gender difference also exists in the analgesia induced by urge‐to‐cough. In this study, we evaluated gender differences in the pain perception response to urge‐to‐cough, as well as to dyspnea. Twenty‐seven male and 26 female healthy nonsmokers were originally enrolled. Citric acid challenge was used to induce the urge‐to‐cough sensation, and dyspnea was elicited by inspiratory loaded breathing. Before and during inductions of these two respiratory sensations, perception of pain was assessed by the thermal pain threshold, and differences between men and women were compared. The thermal pain threshold in women (43.83 ± 0.17°C) was significantly lower than that in men (44.75 ± 0.28°C; P < 0.05) during the baseline period. Accompanying increases in both citric acid concentration and inspiratory resistive load, thermal pain threshold values significantly increased in both men and women. The average thermal pain threshold changes for comparable increases in the urge‐to‐cough Borg score were parallel between men and women. Furthermore, the mean value of the thermal pain threshold plotted against the dyspnea Borg score also showed no significant gender difference. These results demonstrate that although gender differences exist in respiratory sensations, that is, urge‐to‐cough and dyspnea, the inhibitory effects of these respiratory sensations on the perception of pain are not significantly different between the sexes.